2023
DOI: 10.1097/aud.0000000000001370
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Cardiovascular Risk Factors and Audiometric Hearing: Findings From the Canadian Longitudinal Study on Aging

Abstract: Objectives: The objectives of the study were to determine, among a population-based sample of Canadian adults, if risk factors for cardiovascular disease (alone and in combination) were associated with hearing loss. Cross-sectional and longitudinal associations (the latter with about 3 years of follow-up) were examined. Risk factors considered included diabetes, dyslipidemia, hypertension, obesity, and smoking. We also aimed to determine if associations were modified by sex and age group (45 to 54,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
2
5
1
Order By: Relevance
“…We found no association between PTA and 24-hour or daytime BP. This is consistent with a cross-sectional study by Umesawa et al 7 who found no association between hypertension (based on clinic BP measurement) and moderate to severe hearing loss among Japanese workers, and with Mick et al 15 who did not find a cross-sectional association between hypertension (again clinic BP) and PTA at frequencies from 1000 to 4000 Hz in middle-aged and older Canadian adults. Lastly, another study with data from the Korea National Health and Nutrition Examination Surveys did not observe an association between hearing loss and hypertension in participants with normal otoscopy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found no association between PTA and 24-hour or daytime BP. This is consistent with a cross-sectional study by Umesawa et al 7 who found no association between hypertension (based on clinic BP measurement) and moderate to severe hearing loss among Japanese workers, and with Mick et al 15 who did not find a cross-sectional association between hypertension (again clinic BP) and PTA at frequencies from 1000 to 4000 Hz in middle-aged and older Canadian adults. Lastly, another study with data from the Korea National Health and Nutrition Examination Surveys did not observe an association between hearing loss and hypertension in participants with normal otoscopy.…”
Section: Discussionsupporting
confidence: 91%
“…7,8 On the one hand, it has been observed that increased systolic BP (SBP), diastolic BP (DBP), and hypertension were associated with hearing loss and impairment of auditory processing. [9][10][11][12][13] On the contrary, other studies did not observe associations between hypertension and hearing loss, 7,8,14,15 nor with cochlear deterioration. 16 Some age-associated conditions, including disability, 17,18 frailty, 19,20 and dementia, 21,22 have been associated with both hearing loss and hypertension, suggesting that they may have shared mechanisms.…”
mentioning
confidence: 96%
“…In an analysis of data from the Canadian Longitudinal Study on Aging (CLSA), an interaction between age and obesity among women was noted, whereby the association was present among women aged 55 to 64 years, but not in other age groups. In this same study, cross-sectional associations between composite measures of cardiovascular risk and hearing loss were also strongest among 55 to 64 year old women (Mick et al 2021b). Using data from the Health ABC study, Helzner et al (2005) reported that the risk of hearing loss associated with smoking was stronger in Black women (OR = 2.9) versus other sex/race groups, and that the risk associated with hypertension was stronger in White men (OR = 1.3) versus other sex/race groups.…”
Section: Introductionmentioning
confidence: 70%
“…Smoking was the only single factor that was significantly associated with all three audiovestibular symptoms. While in the past an association with smoking has been reported mostly individually for hearing loss (Cruickshanks et al 1998;Lin et al 2013;Tsimpida et al 2019;Engdahl, Stigum, & Aarhus 2021;Tseng et al 2022;Mick et al 2023), tinnitus Biswas & Hall 2021;Goderie et al 2022) and dizziness (Neuhauser et al 2005;Agrawal et al 2009), the underlying cause has not been clarified so far. In an animal model of oxidative stress, degeneration and loss of cochlear spiral ganglion neurons have been documented after chronic exposure to cigarette smoke (Paquette et al 2018).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not certified by peer review) (Tsimpida et al 2019;Biswas & Hall 2021) and obesity (Curhan et al 2013;Hu et al 2020;Biswas & Hall 2021;Mick et al 2023) might be contributing both to hearing loss (Curhan et al 2013;Tsimpida et al 2019;Hu et al 2020;Mick et al 2023) and tinnitus Biswas & Hall 2021). It is remarkable that only smoking seems to be a shared risk factor of all three audiovestibular symptoms hearing loss (Cruickshanks et al 1998;Zhan et al 2011;Lin et al 2013;Tsimpida et al 2019;Engdahl, Stigum, & Aarhus 2021;Tseng et al 2022;Mick et al 2023), tinnitus Biswas & Hall 2021;Goderie et al 2022) and dizziness (Neuhauser et al 2005;Agrawal et al 2009) and might therefore be of particular importance.…”
Section: Introductionmentioning
confidence: 99%